A Randomized Controlled Trial of a Correspondence‐Based Intervention for Carers of Relatives with Psychosis. (27th November 2013) - Deane, Frank P.; Marshall, Sarah; Crowe, Trevor; White, Angela; Kavanagh, David
<x xml:space="preserve">Abstract</x> Background Family members play a crucial role in supporting the recovery of loved ones with psychosis. The journey of recovery is not only traversed by the person experiencing the mental illness but also by their family. Interventions to support these families have traditionally either focused on psychoeducation or addressed problematic interactions or expressed emotion. Family programmes have far less frequently emphasized supporting family members' adjustment to the challenges posed by their relative's disorder or their recovery from associated distress. The study compared a control condition that received only a psychoeducational booklet (Information) and a condition also receiving a correspondence‐based interactive recovery‐oriented intervention (Connections). The Connections group was expected to show greater improvements in recovery knowledge, well‐being, experiences of caregiving, hopefulness and distress. Method A randomized controlled trial was conducted to evaluate the effectiveness of two correspondence‐based family interventions delivered to 81 carers of relatives with psychosis. Results Intent‐to‐treat analyses showed no differential outcomes between conditions, but an analysis of participants who substantially completed their allocated treatment showed that carers receiving Connections had significantly more improvements in well‐being, positive experiences of caregiving and distress. Conclusions Correspondence interventions that support carer's recovery may result in more positive mental health for those who complete key elements of the programme compared with information alone. However, many carers do not complete a correspondence programme and this may limit its impact. Copyright © 2013 John Wiley & Sons, Ltd. Key Practitioner Message A focus on recovery‐oriented interventions holds relevance for carers as well as their loved ones with mental illness. To our knowledge, this is the first randomized controlled trial of a recovery‐focused intervention for carers. Carers may receive positive mental health benefits from recovery‐focused correspondence programmes to the extent that they can be encouraged to remain engaged with such programmes.